Quantifying antimicrobial access and usage for paediatric diarrhoeal disease in an urban community setting in Asia - Le Thi Quynh Nhi; De Alwis, R; Lam, P; Hoa, N; Nhan, N; Le Thi Tu Oanh; Nam, D; Han, BN; Huyen, H; Tuyen, D; Duong, V; Lan, L; et al. (Oxford University Press, 2018)
Objectives Antimicrobial-resistant infections are a major global health issue. Ease of antimicrobial access in developing countries is proposed to be a key driver of the antimicrobial resistance (AMR) epidemic despite a lack of community antimicrobial usage data. Methods Using a mixed-methods approach (geospatial mapping, simulated clients, healthcare utilization, longitudinal cohort) we assessed antimicrobial access in the community and quantified antimicrobial usage for childhood diarrhoea in an urban Vietnamese setting. Results The study area had a pharmacy density of 15.7 pharmacies/km2 (a pharmacy for every 1316 people). Using a simulated client method at pharmacies within the area, we found that 8% (3/37) and 22% (8/37) of outlets sold antimicrobials for paediatric watery and mucoid diarrhoea, respectively. However, despite ease of pharmacy access, the majority of caregivers would choose to take their child to a healthcare facility, with 81% (319/396) and 88% (347/396) of responders selecting a specialized hospital as one of their top three preferences when seeking treatment for watery and mucoid diarrhoea, respectively. We calculated that at least 19% (2688/14 427) of diarrhoea episodes in those aged 1 to ≺5 years would receive an antimicrobial annually; however, antimicrobial usage was almost 10 times greater in hospitals than in the community. Conclusions Our data question the impact of community antimicrobial usage on AMR and highlight the need for better education and guidelines for all professionals with the authority to prescribe antimicrobials.